2017
DOI: 10.1016/j.celrep.2017.11.042
|View full text |Cite
|
Sign up to set email alerts
|

An Elongin-Cullin-SOCS Box Complex Regulates Stress-Induced Serotonergic Neuromodulation

Abstract: Summary Neuromodulatory cells transduce environmental information into long lasting behavioral responses. However, the mechanisms governing how neuronal cells influence behavioral plasticity are difficult to characterize. Here, we adapted the Translating Ribosome Affinity Purification (TRAP) approach in C. elegans to profile ribosome-associated mRNAs from three major tissues and the neuromodulatory dopaminergic and serotonergic cells. We identified elc-2, an Elongin C ortholog, specifically expressed in stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…This likely shows a change in transcriptional priorities and calcium signaling in the simulated cells from cellular metabolic activity signature seen in the unstimulated condition to a more focused genetic signature related to the decoding of external signals. In support of this hypothesis it has recently been demonstrated that the activity of transcription factor Tceb1 is regulated by experience dependent neuronal plasticity driven by specific external stimuli in Caenorhabditis elegans [34]. Tceb1 is a transcriptional regulator of transcription elongation, therefore it has the capacity to be a common regulator of many genes, including calcium signaling genes, which are controlled by neuronal activity firing patterns.…”
Section: Discussionmentioning
confidence: 94%
“…This likely shows a change in transcriptional priorities and calcium signaling in the simulated cells from cellular metabolic activity signature seen in the unstimulated condition to a more focused genetic signature related to the decoding of external signals. In support of this hypothesis it has recently been demonstrated that the activity of transcription factor Tceb1 is regulated by experience dependent neuronal plasticity driven by specific external stimuli in Caenorhabditis elegans [34]. Tceb1 is a transcriptional regulator of transcription elongation, therefore it has the capacity to be a common regulator of many genes, including calcium signaling genes, which are controlled by neuronal activity firing patterns.…”
Section: Discussionmentioning
confidence: 94%
“…Table S6). In contrast, only 6/119 and 1/119 up-regulated genes were present in the muscle and neuronal TRAP data sets (Gracida et al, 2017), respectively (Fig. 5D, Supp.…”
Section: Gene Expression Is Perturbed In Csr-1a Mutantsmentioning
confidence: 93%
“…Conversely, the genes displaying increased expression showed a weak association with muscle, intestine, and neuronal GO terms (data not shown). To understand which tissues or processes the upregulated genes were associated with, we examined several additional datasets, including modENCODE mRNA-seq data from each stage of development, Translating Ribosome Affinity Purification (TRAP) data from muscles, neurons, and intestines (Gracida et al, 2017), and sperm proteome data (Ma et al, 2014) (Supp. Table S6).…”
Section: Gene Expression Is Perturbed In Csr-1a Mutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…30 infection. Similarly, exposure to increasing temperatures enhances 5-HT release from the 54 serotonergic neurons (called NSM and ADF neurons) through the activity of the animal's 55 thermosensory neurons (called AFD neurons) and this release of 5-HT cell non-autonomously 56 protects the animal from proteotoxicity (Gracida, Dion, Harris, Zhang, & Calarco, 2017; Iwanir 57 et al, 2016; Shao et al, 2019; Tatum et al, 2015a). However, whether 5-HT released by the 58 parent upon the detection of stress protects germ cells and future progeny from stress is not 59 known.…”
mentioning
confidence: 99%